ENGLISH AS A FOREIGN LANGUAGE. WHAT CHALLENGES DO TEACHERS OF ENGLISH FACE? - Silvia IRIMIEA (Studia Universitatis Babeş-Bolyai: Geographia, 2016)
English as a Foreign Language. What Challenges Do Teachers of English Face? The article undertakes to suggest ways in which English as a foreign language should be taught as a consequence of English becoming a global language and its being spoken in different parts of the world. The article goes out from three prerequisites: David Crystal’s statement that the ‘the greatest challenge for the teachers’ is that ‘they must keep pace with the language change, given that languages change so fast’(2013), it is studied and used everywhere in the world, and the need to eliminate the mismatch between the language taught in the classroom and the language spoken by natives or in professional environments. The present study is focused on the discussion of textbooks, the variety of English to be taught, cultural background, and pronunciation issues.